OUTCOMES OF DISTAL FEMUR FRACTURE TREATED WITH DYNAMIC CONDYLAR SCREW - Naeem ur Razaq, Muhammad; Muhammad, Taj; Ahmed, Ashfaq; Adeel, Muhammad; Ahmad, Sajjad; Ahmad, Saeed; Sultan, Shahid (Journal of Ayub Medical College Abbottabad, 2016)
Background: Implants for open reduction and internal fixation of distal femoral fracture includes angle blade plate, rush nails, enders nail and interlocking nails. But all these devices are technically demanding and less effective in providing inter-fragmentary compression in osteoporotic bones. These problems can be solved with dynamic condylar screw (DCS).The objective of the study was to determine the frequency of different outcomes of distal femoral fracture treated with dynamic condylar screw Methods: This case series study was carried out in the Department of Trauma & Orthopaedics, Ayub Teaching Hospital Abbottabad from 1st October 2014 to August 2015, after approval of the ethical committee of the institution. Data of all patients with distal femoral fractures aged 20-70 years, recruited through emergency, OPD or consultant clinic collected on a pro forma. Standard treatment of trauma was given to the patients. Detailed history was taken including the past medical and surgical history. Detailed examination including air-way, breathing and circulation, general physical examination and abdomino-pelvic examination was done in each patient. Investigations including urinalysis, haemoglobin %, full blood count, X-ray (both AP and lateral view) of the involved femur (including hip and knee) was done. Results: Mean age of the patients was 43.18±14.647 ranging from 20 to 70 years. Mean duration of hospital stay in days was 2.21±1.111 ranging from 1 to 6 days. Patients' follow-up assessment after 4 months of surgery for union of femoral fracture treated with dynamic condylar screw was found in 96 (94.1%), wound infection was found in 7 (6.9%), knee stiffness was found in 21 (20.6%) and limb shortening was found in 7 (6.9%). Conclusion: Dynamic condylar screw is an easy, scientifically less difficult and satisfying method of treatment for fractures of femur. Keywords: Distal Femur Fracture, Dynamic Condylar Screw,Internal fixation